Assessment of Biochemical Changes Among Covid-19 Cases in a Tertiary Hospital of Bangladesh During Early Pandemic (Journal of Preventive and Social Medicine, 2022)
Background: Corona virus disease 2019 (COVID-19) involves various organs of the body causing several biochemical changes which plays an essential role in estimating the patients’ condition and prognosis, directing treatment, and even evaluating the curative effects. The present study aimed to assess the biochemical changes among the COVID-19 patients during early pandemic.Methods: This cross sectional study was conducted at Combined Military Hospital (CMH) Dhaka among purposively selected 237 confirm COVID-19 cases. Data were collected through face to face interview and review of medical records using a pre-tested semi-structured questionnaire. The study was conducted in the Combined Military Hospital Dhaka from 15 April 2020 to 31 May 2020Results: Highest number of the respondents were in the age group of 31-40 years (37.1%) with male predominance (83.1%). About 95.6% were Muslim and 58.6% were educated up to secondary level. About 87.8% had contact with a confirmed case and having 47.7%, 37.2%, 15.1% cardiovascular, endocrine and respiratory comorbidities respectively. Fever (34.6%) was the most common presenting symptoms followed by cough (22.9%), sore throat (10.6%). Neutrophilia observed in 26.16%, lymphopenia in 20.7%, thrombocytopenia in 14.3% cases, 30.0% with positive D-dimer test, 22.4% either sepsis or systemic infection in procalcitonin estimation, 28.3% with increased ferritin, 28.7% with positive C reactive protein, 21.1% with increased LDH. Chi-square analysis revealed a statistically significant association between cardiovascular and endocrine diseases with several biochemical changes (p